PENGARUH MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANREG XII BKN PEKANBARU - Tumiati "; Rusli Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Abstract : Effect Of Motivation On Employees Performance In Office StaffingAgency State Region XII (Bkn)Pekanbaru. The research was conducted at theRegional Office XII of the State Personnel Board (BKN) Pekanbaru . The purpose ofthis study was to determine the effect of work motivation on employee performance atthe Regional Office XII of the State Personnel Board ( BKN ) Pekanbaru . Thehypothesis of this study is alleged there is an influence of employee motivation onemployee performance . This study uses quantitative and qualitative analysis usingmultiple linear regression analysis with the help of SPSS software version 18.0.Theresearch data was obtained from the data documentation existing in the organization .Population and samples in this study were employees of the Regional Office XII of theState Personnel Board (BKN) Pekanbaru with a total sample of 52 respondents usingcensus method . Based on the scores obtained from the results of the study indicatethat there is significant between work motivation on employee performance , with acorrelation coefficient of 0.897 obtained are included in the category of very strongwith an error level of 5 % . This suggests that Ho is rejected , H1 is accepted andemployee motivation variable has a positive influence on employee performance at theRegional Office XII of the State Personnel Board ( BKN ) Pekanbaru . While themagnitude of the effect between the independent variable (X) to variable (Y) based onthe calculation of the coefficient of determination equal to 11.779 so that it can be seenthat the work motivation variables accounted for 94.7 % of the employee 'sperformance at the Regional Office XII of the State Personnel Board (BKN)Pekanbaru .Key Word: Motivasi Kerja, Kinerja pegawai, Organisasi